Análise dentária tridimensional em pacientes biprotrusos submetidos a extrações de primeiros pré-molares - Cunha, Anderson Farias da [UNESP] (2018)
Objetive: To evaluate the dental changes in patients bimaxillary protrusion with first premolar extraction. Methods: Fifty adults patients Class I malocclusion, dental protrusion, arch length discrepancy bellow for 4mm, and need for first premolar extractions were randomized to 2 treatment techniques: en-mass retraction (n = 25) and two-steps retraction (n = 25, patients had either conventional or self-ligating brackets bonded to canines randomly). Digital models before, and one, two, three months after starting the canine retraction, and after the closing of space. Were evaluated the canine inclination, angulation and rotation (canine retraction), and rotation of the upper first molars (en-mass or two-steps retraction). Results: No differences were found between retraction techniques or the type of bracket. Conclusions: Angulation, inclination and rotation showed no diferences between conventional or self-ligating brackets, besides that the rotation molar was similar in enmass or two-steps retraction.